Reaction Stability Test of Hexavalent Chromium Complex with 1,5-Diphenylcarbazide in Analysis using UV Visible Spectrophotometer - Warmiati, Warmiati; Wijayanti, Wijayanti (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
A reaction stability test of hexavalent chromium complex with 1,5-diphenyl carbazide in analysis using a UV Visible Spectrophotometer has been done in this study. This study aims to find out the colored complex stability for the reaction of chromium hexavalent and diphenyl carbazide in the analysis of hexavalent chromium using a UV Vis spectrophotometer in terms of time. The sample was measured in 540 nm of wavelength with 10, 30, 60, 90, 120, and 180-minute time intervals. Each interval was carried out with two times replications. There were no significant differences in the colored complex until the 180-minute time interval, and the measurement of Cr(VI) concentration showed similar results. This analysis exhibits a level of precision and accuracy, evident from the RPD values below 10 % and the recovery values falling within the range of 90 – 110 %. It means that the reaction of hexavalent chromium complex with 1,5-diphenyl carbazide in analysis using a UV Visible Spectrophotometer is stable.